Respostas
respondido por:
1
Olá!!
Fórmula: an = a1.q^(n-1)
Onde:
an = 62500
a1 = 4
n = ???
q = 5
62500 = 4.5^(n-1)
62500/4 = 5^(n-1)
15625 = 5^(n-1)
5^6 = 5^(n-1)
6 = n-1
6 + 1 = n
7 = n
A P.G possui 7 termos.
★Espero ter ajudado!! tmj
Fórmula: an = a1.q^(n-1)
Onde:
an = 62500
a1 = 4
n = ???
q = 5
62500 = 4.5^(n-1)
62500/4 = 5^(n-1)
15625 = 5^(n-1)
5^6 = 5^(n-1)
6 = n-1
6 + 1 = n
7 = n
A P.G possui 7 termos.
★Espero ter ajudado!! tmj
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás